Band notched self complementaryultra wideband antenna for wireless applications - Ramakrishna, Ch; A.E.Satish Kumar, G; Chandra Sekhar Reddy, P (International Journal of Engineering and Technology, 2018)
This paper presents a band notched WLAN self complementaryultra wide band antenna for wireless applications. The proposed antenna encounters a return loss (RL) less than -10dB for entire ultra wideband frequency range except band notched frequency. This paper proposes a hexagon shape patch, edge feeding, self complementary technique and defective ground structure. The antenna has an overall dimensionof 28.3mm Ã— 40mm Ã— 2mm, builton Â substrate FR4 with a relative dielectric permittivity 4.4. And framework is simulated finite element method with help of high frequency structured simulator HFSSv17.2.the proposed antenna achieves a impedance bandwidth of 8.6GHz,Â band rejected WLAN frequency range 5.6-6.5 GHz withÂ vswr is less than 2.